2012
DOI: 10.1016/s0924-9338(12)75231-8
|View full text |Cite
|
Sign up to set email alerts
|

P-1064 - Cycloid psychoses: Leonhard's descriptions revisited

Abstract: Introduction: Cycloid psychoses (CP) as described by Leonhard comprise the subtypes anxiety-happiness, confusion and motility psychoses. CP presents with an acute onset and have a favourable prognosis. The operational criteria by Perris and Brockington (P&B, 1981) are partly incorporated in ICD-10 as acute polymorphic psychosis (APP). The DSM-IV category Brief Psychotic Disorder (BPD) includes all psychoses with short duration. Objectives: Establishing concordance of Leonhard´s CP with DSM-IV and ICD-10 catego… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…That group also found that the diagnoses that were most similar to cycloid psychosis were the International Classification of Diseases, 10th Revision (ICD-10) diagnoses of schizoaffective disorder and acute and transient psychotic disorder, and the DSM-IV diagnosis of brief psychotic disorder. When compared with these 3 disorders, the Perris and Brockington criteria were found to have the highest concordance rate with the original 3-subtype description of cycloid psychosis delineated by Karl Leonhard, supporting the concept as clinically useful and distinct 17 . We break down these 3 disorders, using DSM-5 and ICD-10 criteria where available for clinical relevance, 18,19 and compare them with the Perris and Brockington diagnostic criteria of cycloid psychosis in Table 2 4,20,21 .…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…That group also found that the diagnoses that were most similar to cycloid psychosis were the International Classification of Diseases, 10th Revision (ICD-10) diagnoses of schizoaffective disorder and acute and transient psychotic disorder, and the DSM-IV diagnosis of brief psychotic disorder. When compared with these 3 disorders, the Perris and Brockington criteria were found to have the highest concordance rate with the original 3-subtype description of cycloid psychosis delineated by Karl Leonhard, supporting the concept as clinically useful and distinct 17 . We break down these 3 disorders, using DSM-5 and ICD-10 criteria where available for clinical relevance, 18,19 and compare them with the Perris and Brockington diagnostic criteria of cycloid psychosis in Table 2 4,20,21 .…”
Section: Discussionmentioning
confidence: 71%
“…When compared with these 3 disorders, the Perris and Brockington criteria were found to have the highest concordance rate with the original 3-subtype description of cycloid psychosis delineated by Karl Leonhard, supporting the concept as clinically useful and distinct. 17 We break down these 3 disorders, using DSM-5 and ICD-10 criteria where available for clinical relevance, 18,19 and compare them with the Perris and Brockington diagnostic criteria of cycloid psychosis in Table 2. 4,20,21 Unlike brief psychotic disorder, a mood component can fulfill the criteria for cycloid psychosis, and the duration of the episode is not limited to less than 1 month.…”
Section: Diagnostic Validitymentioning
confidence: 99%
“… 32 , 33 PANSS cognitive score was calculated according to the procedure as described by Lindenmayer et al 34 To establish diagnosis of CP, a symptom checklist according to Leonhard was completed by NvdK and a clinician (MKF Schneider) trained in establishing diagnoses according to Leonhard. 26 , 30 , 35 Final diagnoses were made in a so-called Longitudinal Evaluation of All Data (LEAD) conference, in which all possible and probable cases of CP were discussed with two experts in the field of CP (GS and WV). 36…”
Section: Methodsmentioning
confidence: 99%
“… 21 23 CP, as such, are not included in the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition (DSM-IV), although pananxiety, perplexity, and motility disorders have been demonstrated in a substantial percentage of patients. 24 – 30 An overview of the characteristics of schizophrenia and CP is presented in Table 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Cycloid psychoses are characterized by polymorphic symptomatology with intraphasic bipolarity, a remitting and recurrent course and favorable prognosis 1,2 . Despite its clinical relevance, the cycloid psychoses concept has been relatively neglected in current psychiatric nosological systems 2 .…”
Section: Introductionmentioning
confidence: 99%